Your Phone or Mine?: Fusing Body, Touch and Device Sensing for Multi-User Device-Display Interaction - Tansley, Stewart; Wilson, Andy; Brush, A.J. (CHI '12 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2012)
Determining who is interacting with a multi-user interactive touch display is challenging. We describe a technique for associating multi-touch interactions to individual users and their accelerometer-equipped mobile devices. Real-time device accelerometer data and depth camera-based body tracking are combined to associate each phone with a particular user, while body tracking and touch contact positions are combined to associate touch contacts with a specific user. It is then possible to associate touch contacts with specific devices, allowing for more seamless device-display interactions in a multi-user scenario. We describe the implementation and present a user study with 14 people to validate and demonstrate a content exchange application using this approach.